Reporting on Sustainability Standards in Australia: Focus on ISO 14001 - Naudé, Marita; Quaddus, Mohammed; Rowe, Anna; Nowak, Margaret (Greenleaf publisher, 2013)
There is a worldwide demand for companies to report on their environmental engagement. This study aimed to gain understanding in the differences between IS014001 certified and ISO 14001 non-certified companies with regard to their environmental reporting. The researchers used a combination of website searches and content analysis for the data collection. There was a notable difference whereby the majority of IS014001 certified companies provide easily findable information on the company website compared with the majority of IS014001 non-certified companies for which the information was hidden. Another notable difference was that 33.3% of IS014001 certified companies demonstrated outstanding disclosure of targets and outcomes compared with 11.6% of the ISO 14001 non-certified companies. It was clear that both the IS014001 certified and IS014001 non-certified companies engage in similar programmes: namely, social, management, technical/technological, community training, community engagement and HR programmes. The most notable difference related to HR programmes where 88.1% of ISO 14001 certified companies engaged in these programmes compared with 38.3% of ISO 14001 non-certified companies. The paper concludes with both research and management implications.